2014
DOI: 10.1159/000360235
|View full text |Cite
|
Sign up to set email alerts
|

Thalassemia Major and Sickle Cell Disease in Adolescents and Young Adults

Abstract: The increased longevity of patients with thalassemia and sickle cell disease (SCD) introduces new clinical challenges due to the accumulation of disease-related morbidity, psychosocial issues and health care adjustments. Patients with thalassemia major now live into adulthood without suffering heart failure but must confront delayed puberty, impaired fertility and progressive bone disease. The increased survival in SCD brings to the front previously unrecognized complications including pulmonary hypertension, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
2
8
0
2
Order By: Relevance
“…On the other hand, all forms of treatment can be inconvenient, time-consuming, and result in unpleasant side effects, all which could potentially impact physical and emotional functioning of patients. [ 2 3 6 9 13 14 30 34 ] In our study, the DFX-treated pediatric and adult patients with BTM or SCA were heavy iron overloaded in agreement with previous reports. [ 20 26 35 36 37 38 39 40 41 42 ] The lack of treatment may explain the high ferritin levels.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, all forms of treatment can be inconvenient, time-consuming, and result in unpleasant side effects, all which could potentially impact physical and emotional functioning of patients. [ 2 3 6 9 13 14 30 34 ] In our study, the DFX-treated pediatric and adult patients with BTM or SCA were heavy iron overloaded in agreement with previous reports. [ 20 26 35 36 37 38 39 40 41 42 ] The lack of treatment may explain the high ferritin levels.…”
Section: Discussionsupporting
confidence: 92%
“…Thalassemia patients had lower BMI due to many factors such as growth hormone deficiency, hypothyroidism, hypogonadism, low Hb levels, bone disorders and desferrioxamine toxicity. 45,46 This result corresponds to prior study by Estrella-Castillo et all that showed subjects with lower weight have poorer cognitive compared to normal population. 47 Study by Joo et all concluded that subjects that have lower BMI has progressive risk to have Alzheimer's compared to normal 13 while Suemoto et all showed that decrease BMI leads to decreased of memory function within 12 years.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, sickle cell patients with HbSS genotypes had their menarche late at 16 years of age. Puberty delay is usually observed in SCD and is proportional to the severity of the disease 18. The delivery was programmed at the 37th week; this attitude is the one reported by many authors 19,20.…”
Section: Discussionmentioning
confidence: 85%